IMPLEMENTASI NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP SWASTA RAKYAT SEI GLUGUR KECAMATAN PANCUR BATU - Rahmatul Aufa, Syamsu Nahar, Salminawati (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2019)
Abstrak: This study aims to analyze: 1) the implementation multicultural education in the subject ofIslamic Religion Education in Rakyat independent Junior High School Sei Glugur district PancurBatu. 2) the constraints of Islamic Religion Education in implementing the multicultural education inthe lessons of Islamic Religion Education in Rakyat independent Junior High School Sei Glugurdistrict Pancur Batu. 3) the efforts of Islamic Religion Education in implementing the multiculturaleducation in the lessons of Islamic Religion Education in Rakyat independent Junior High SchoolSei Glugur district Pancur Batu. This type of research is qualitative with a narrative approach, namelyresearch procedures that produce descriptive data in the form of written or oral words of observedbehavior. The results of the study show that: 1) Implementation of the planting of multicultural educationin the subject of Islamic Religion Education at the peoples private junior high school by providinggood examples of teachers about interrelated by not discriminating between students who are onlywith others students. 2) Related to the challenges that were issued by the public private junior highschool Islamic Religion Education teacher Sei Glugur in implementing the multicultural education,namely: Lack of awareness of students in good fighting, Lack of support for parents of students, Lackof media that can be visited, No need for values images multicultural advocates, and the difficulty ofdetermining the time to disseminate multicultural values from experts needed from outside the schoolfor all students. 3) Efforts of Islamic Religion Education in implementing the multicultural education inSei Glugur Pancur Batu private middle school are as follows equalizing the majority and contributing,minimizing conflicts in school for the purpose, mission and purpose of the school, so that teachers aremore proficient in complaint plan learning and decision method/ strategy decisions.